Histopathology of tympanic membranes from patients with ventilation tubes. Issue 3 (June 2018) - Oktay, Mehmet Faruk; Tansuker, Hasan Deniz; Fukushima, Hisaki; Paparella, Michael M.; Schachern, Patricia A.; Cureoglu, Sebahattin
Abstract: Objective: To evaluate the histopathologic changes in tympanic membranes (TMs) with ventilation tubes (VTs). Methods: In this retrospective human temporal bone study our overall study group included 4 subgroups of TMs from deceased donors as follows: 24 with a history of VT insertion for chronic otitis media with effusion (COME-VT); 5 with a history of VT insertion for Meniere's disease (MD-VT); 33 without a history of VT insertion for chronic otitis media with effusion (COME); and 14 without a history of VT insertion for Meniere's disease (MD). We classified the extent of migration of the outer keratinized squamous epithelium onto the inner surface of TM perforations and noted the presence and location of tympanosclerosis, of atrophy, of perforation, and/or of cholesteatoma formation. Results: Tympanosclerosis occurred in 14/24 TMs in the COME-VT subgroup; 2/5, MD-VT; 7/33, COME; and 0/14, MD. The VT insertion site was mostly in the anteroinferior (63%) quadrant of the TM; tympanosclerosis occurred more frequently in the posteroinferior (42%) and posterosuperior (33%) quadrants. We found no significant correlation between the location of tympanosclerosis and the VT insertion site ( P > 0.05). Atrophy occurred in 7/24 TMs in the COME-VT subgroup; 3/5, MD-VT; 8/33, COME; and 2/14, MD. We found no significant correlation between the location of atrophy and the VT insertion site; however, atrophy was located mostly in the anteroinferior quadrant (one of the most common VT insertion sites) of the TM. Regarding the ingrowth of keratinized epithelium, the mucocutanous junction was detected at any point at the inner surface of the TM in 50% of the specimens. We observed intratympanic cholesteatoma formation in 2/24 TMs in the COME-VT subgroup. Conclusion: TM changes due to VT insertion are more common than previously realized. Meticulous otomicroscopic evaluation of the TM is necessary during tympanomastoidectomies in order to prevent the intratympanic inclusion pearls and squamous epithelial ingrowth to prevent any further cholesteatoma formation.